Novel humidity sensitive materials derived from naphthalene-based poly (arylene ether ketone) containing sulfobutyl pendant groups. (10th April 2016) - Qi, Duo; Zhao, Chengji; Zhuang, Zhuang; Li, Guibin; Na, Hui
Highlights: Novel side-chain type sulfonated poly (arylene ether ketone)s were prepared, and the Ds can be controlled precisely. The water sorption behaviour of the polymers has been discussed from the mechanism. The effect of the structure on the humidity sensitivity properties has been discussed in detail. High Ds materials show excellent sensitivity and stability in a wide humidity range. Abstract: A series of novel side-chain-type sulfonated polymer aromatic electrolytes (PAEK-SO3 Na- x ) with different sulfonation degrees (Ds) were synthesized through a polycondensation of 1, 5-bis(4-fluorobenzoyl)-2, 6-dimethoxynaphthalene and hydroquinone, followed by a demethylation and sulfobutylation reaction. The structures and Ds of the polymers were confirmed by their 1 H NMR spectra and the hydrophilic nature of the membranes was characterized by water uptake and contact angle test. A dual-mode sorption model was applied to analyze the water vapor sorption of the polymers. Humidity sensors were prepared from PAEK-SO3 Na- x . Then the sensitivity and responsibility of the sensors were characterized in detail. The variation range of the impedance of the sensors was from 10 7  Ω to 10 2  Ω between 11% RH and 97% RH, which was wider than many other polymeric humidity sensors reported and indicated a good sensitivity. The response time of PAEK-SO3 Na-80 was 90 s and 100 s for desorption and adsorption, respectively. It is for the first time to apply side-chain-type sulfonated polymer electrolyte to humidity sensors and this new kind of sensitivity material showed a good application prospect.